2016
DOI: 10.1007/s00704-016-1829-3
|View full text |Cite
|
Sign up to set email alerts
|

Building global and diffuse solar radiation series and assessing decadal trends in Girona (NE Iberian Peninsula)

Abstract: Measurement of solar radiation was initiated in Girona, northeast of the Iberian Peninsula, in the late 1980s. Initially, two pyranometers were installed, one of them equipped with a shadowband for measuring the diffuse component. Two other pyranometers currently exist, both ventilated and one of them shadowed, with a sphere, and a pyrheliometer for measuring direct radiation. Additional instruments for other shortwave and longwave components, clouds, and atmospheric aerosols have been installed in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
1
11
0
1
Order By: Relevance
“…Similarly, an average upward trend of about 3.9 W m −2 per decade was reported for the period of 1985-2010 in Spain (Sanchez-Lorenzo et al, 2013. Calbo et al (2016) also observed a significant upward trend in the mean annual R S records of 1987-2014 in Girona (Spain). Rahimzadeh et al (2015) analysed the duration of sunshine hours in Iran for the period of 1961-2009 and reported that despite an increase in the rate of sunshine hours from the early 1980s to the end of 20th century, a renewed dimming is observed during the 2000s in Iran, with a sharp drop in 2009.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similarly, an average upward trend of about 3.9 W m −2 per decade was reported for the period of 1985-2010 in Spain (Sanchez-Lorenzo et al, 2013. Calbo et al (2016) also observed a significant upward trend in the mean annual R S records of 1987-2014 in Girona (Spain). Rahimzadeh et al (2015) analysed the duration of sunshine hours in Iran for the period of 1961-2009 and reported that despite an increase in the rate of sunshine hours from the early 1980s to the end of 20th century, a renewed dimming is observed during the 2000s in Iran, with a sharp drop in 2009.…”
Section: Introductionsupporting
confidence: 65%
“…Calbo et al . () also observed a significant upward trend in the mean annual R S records of 1987–2014 in Girona (Spain). Rahimzadeh et al .…”
Section: Introductionmentioning
confidence: 99%
“…The site is located in the northeast of the Iberian Peninsula, some 30 km from the Mediterranean Sea and 40 km from the Pyrenees mountain range; the climate is Mediterranean, meaning mild winters and hot summers, and relatively dry, with more rain in equinoctial seasons. Characteristics of the site and of instruments of this station can be found in Calbó et al (2016); here we will only give some details of the relevant instruments used in the current research. First, the site holds a set of instruments measuring downwelling shortwave (solar) and longwave (atmospheric) radiation, including the three components for the solar irradiance (global, direct, and diffuse).…”
Section: Data Measurements and Observationsmentioning
confidence: 99%
“…To test the potentialities and drawbacks of the method, a short campaign, described in Table 1, was run in the spring of 2015, in the Polytechnic School of the University of Girona, where data from a radiometric and meteorological station are available [5]. Variable sky conditions were observed along the campaign: cloudless, highlevel cloudiness (cirrus), scattered-to-broken sky cover, and overcast.…”
Section: Early Results From a Campaignmentioning
confidence: 99%